Poisonous Roots - Modiboa , Boitshepo (Open Mic: A Creative Writing Journal, 2024)
"Poisonous Roots" is a poem about domestic abuse and it’s consequences. It explores the long lasting impact of childhood trauma and shows us that pain can be passed down.